2005
DOI: 10.1111/j.1525-1470.2005.22404.x
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Balanitis Xerotica Obliterans in Boys with Phimosis: Prospective 10‐Year Study

Abstract: This prospective study was designed to address the incidence and clinical and histologic characteristics of balanitis xerotica obliterans in a large random pediatric population with phimosis. We investigated 1178 boys who presented consecutively with phimosis between 1991 and 2001. All patients who underwent complete circumcision and surgical specimens were typed histologically as early, intermediate, or late forms of this disorder or as nonspecific chronic inflammation. Patients with balanitis xerotica oblite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
7
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 22 publications
7
91
7
7
Order By: Relevance
“…Although once thought to affect only 1% of boys, (90) recent histological examination of the prepuce from 1178 boys circumcised for phimosis found BXO in 40%. (91) Of these, 19%…”
Section: Balanoposthitismentioning
confidence: 99%
See 1 more Smart Citation
“…Although once thought to affect only 1% of boys, (90) recent histological examination of the prepuce from 1178 boys circumcised for phimosis found BXO in 40%. (91) Of these, 19%…”
Section: Balanoposthitismentioning
confidence: 99%
“…Incidence peaked at ages 9-11 (76% of cases). (91) Of 41 paediatric BXO cases in Boston, 52% had been referred for phimosis, 13% for balanitis and 10% for buried penis. (92) Of the 46% who were subsequently circumcised, BXO was found in the meatus of 27%.…”
Section: Balanoposthitismentioning
confidence: 99%
“…The incidence of the condition is unknown, but most authors agree it is increasing and many cases of phimosis undergoing non-elective circumcision in childhood might be in fact have undiagnosed BXO. [15] Consistently, it was reported that approximately half of prepuces obtained from nonelective circumcisions were consistent with a diagnosis of BXO. [16,17] BXO is diagnosed by histological features including hyperkeratosis and hyperplasia of the squamous mucosa along with homogenous collagen deposition in the upper dermis.…”
Section: Review Articlementioning
confidence: 67%
“…[16,17] BXO is diagnosed by histological features including hyperkeratosis and hyperplasia of the squamous mucosa along with homogenous collagen deposition in the upper dermis. [15] Clinically, the condition can be suspected in the presence of a white, sclerotic, distal preputial ring (Fig. 1B).…”
Section: Review Articlementioning
confidence: 99%
“…Zabieg obrzezania jest skuteczny w przypadku zmian LS zlokalizowanych na napletku i żołędzi [42][43][44]. W przypadku LS z dużymi zmianami zarostowymi utrudniającymi oddawanie moczu wykonuje się operacje ujścia cewki moczowej lub całej cewki moczowej usprawniające funkcjonowanie narządu [43,[45][46][47][48].…”
Section: Leczenie Drugiego Rzutuunclassified